THE COLONIALITY OF LANGUAGE: RACE, EXPRESSIVITY, POWER, AND THE DARKER SIDE OF MODERNITY. - Veronelli, Gabriela A. (Wagadu: A Journal of Transnational Women's & Gender Studies, 2015)
This article presents a new framework to analyze linguistic relations of power that examines the linguistic effects of what Aníbal Quijano has theorized as "the coloniality of power." The argument is organized in two sections. The first section introduces "the coloniality of language," an expression the author uses to refer to the process of racialization of colonized populations as communicative agents beginning in the sixteenth century and continuing until today. This section includes an account of the language and communication paradigm being developed at the time of the Conquest, which, the author argues, contains the coloniality inside. In the second section, the author proposes to shift paradigms to get outside the "conceptual and social prison" of modernity/coloniality and understand colonized-colonialized languages and colonized-colonialized speakers differently. The conclusion illustrates some ideas and concerns about accessing and fostering decolonial alternatives that come forth from the article's critical analysis.